Single tooth osteotomy and distraction in the treatment of an ankylosed central incisor - a case report - Mayne Robert; Mayne Roslyn; Saranathan Sathyan; Spencer Kevin (Sciendo, 2017)
Clinical practice encounters the unfortunate consequences of dental trauma. The avulsion of permanent teeth is seen in 0.5-3% of all dental traumatic injuries, and when re-implanted, a tooth can undergo ankylosis in the form of replacement resorption. When ankylosis of a maxillary incisor occurs in a pre-adolescent, the affected tooth gradually becomes infra-occluded with time, which results in severe local dentoalveolar disturbances in normal growth and development, along with aesthetic concerns that challenge orthodontic management. To achieve an ideal dental outcome, an interdisciplinary approach is often required.